Vision status: presbyopic patient undergone corneal inlay procedure - Linsay Sundram Gnanasundram,; Rokiah Omar,; Bashirah Ishak,; Low, Aloysius Joseph (Penerbit UKM, 2016)
This study reports the vision status of a presbyopic patient who has undergone a corneal inlay procedure. The study hopes to provide optometrists more insight on the procedure and the co-management involved in such a patient. The patient, a 48 years-old Chinese woman with presbyopia underwent the corneal inlay procedure three years ago. She had the inlay implanted in the non-dominant eye to aid near vision i.e. her left eye. The pre and post-operative evaluations include distance and near visual acuity, fundoscopy, tonometry, Schirmer’s test, slit lamp evaluation, corneal topography and corneal pachymetry. Near visual acuity for the left eye improved from N14 to N5 immediately after the procedure. Even after 3 years of post-operative followup, the patient was still able to maintain her near vision. In conclusion, the corneal inlay procedure helped to improve near vision of this presbyopic patient. Optometrist plays a very important role in the co-management of such patients alongside with the ophthalmologist in terms of visual functional assessments pre and post-surgery, counseling of the procedure and managing patients’ expectations.